Transparansi Informasi sebagai Bentuk Perlindungan Konsumen di Sektor Jasa Keuangan: Studi Komparasi di Indonesia, Singapura, dan Malaysia - Trigaya Ahimsa (Dialogia Iuridica, 2022)
Abstract : Based on the data disclosed by Otoritas Jasa Keuangan (Financial Services Authority) as the supervisory body of the financial services sector, throughout 2020 and 2021, there are thousands of complaints regarding information provided and conveyed by financial services providers. This matter shall be observed carefully, since transparency of information is one of the principles commonly recognized in consumer protection field, both generally and in the financial services sector specifically. The transparency of information principle also directly correlates with the principle of responsible business conduct. The transparency of information regarding financial products and/or services may give the consumers a fair chance to compare said products and/or services, and to assess whether the products and/or services really fit the consumers’ needs. This study aims to dig deeper about the transparency of information principle regarding financial products and/or services, based on the domestic rule and international best practices. This study also compares the rules on the subject of transparency of information regarding financial products and/or services in Indonesia against the rules in Singapore and Malaysia. In this research, it has been found that the existing regulations are sufficient enough, although the regulator shall strengthen the supervisory effort, including the imposition of sanctions. Keywords : Consumer; Financial Services Sector; Transparency